Pengaruh Pupuk Organik Cair (POC) Teknologi Nano terhadap Pertumbuhan Pakcoy (Brassica rapa L.) yang Dibudidayakan secara Hidroponik - Putri, Afriani Amelia; Fevria, Resti (MASALIQ, 2024)
The use of AB Mix in hydroponic cultivation has side effects on body health because AB Mix is a chemical fertilizer. Liquid organic fertilizer is fertilizer in liquid form made from a mixture of compost and fermented water which can provide nutrients according to plant needs. Providing nutrients in hydroponic cultivation has a weakness, namely that nutrient deposition occurs, especially when using a wick system because the nutrients in the wick system are passive. To reduce the deposition of nutrient solutions in the wick system used in this research, nanotechnology is needed which can reduce the particle size so that it is more efficient use of nutrients. This research used the RAL method with 3 treatments and 5 repetitions P1 Control (AB Mix 100%), P3 AB Mix 50% + POC nano 50%, P5 POC nano 100%. The observation data obtained was analyzed using the ANOVA (Analysis of Variance) test using the SPSS (Statistical Package for the Social Sciences) application. And continued with the DMRT test at the 5% level. The results obtained from the influence of POC nanotechnology on the growth of pakchoy plants can be seen from the average height of P1 plants, namely 17.44 cm, number of leaves 28.2, wet weight 32.44 g, and dry weight 2.1 g. The use of POC nano technology does have effect on the growth of pakchoy plants.